Augustus Hopkins Strong and the struggle to reconcile Christian theology with modern thought - Aloisi, John (Book collections on Project MUSE., 2021)
"Augustus Hopkins Strong was the president of Rochester Theological Seminary for 40 years (1872-1912). Although Strong regarded himself as a theological conservative, he oversaw the transition from orthodoxy to a much more modern view of theology at Rochester. Over the course of his academic career, Strong's theology evolved as he sought to facilitate an ideological rapprochement between Christian orthodoxy and modern thought. This book traces the evolution of Strong's theology, particularly its movement in the direction of philosophical idealism and arguably pantheism. This book argues that Strong's theological journey and embrace of ethical monism was his attempt to bring together theological conservatives and modernists while trying to resolve tensions within his own thinking. In the end, Strong was unable to persuade modernists to embrace ethical monism or to convince conservatives that ethical monism was a legitimate theological option. Strong's attempt at a theological synthesis failed due largely to the contradictions which ethical monism produced within both Christian theology and philosophical monism. But Strong's journey had a significant impact on the direction of Rochester Theological Seminary"--